2012
DOI: 10.1182/blood-2012-01-405365
|View full text |Cite|
|
Sign up to set email alerts
|

A foundation for universal T-cell based immunotherapy: T cells engineered to express a CD19-specific chimeric-antigen-receptor and eliminate expression of endogenous TCR

Abstract: Clinical-grade T cells are genetically modified ex vivo to express a chimeric antigen receptor (CAR) to redirect specificity to a tumor associated antigen (TAA) thereby conferring antitumor activity in vivo. T cells expressing a CD19-specific CAR recognize B-cell malignancies in multiple recipients independent of major histocompatibility complex (MHC) because the specificity domains are cloned from the variable chains of a CD19 monoclonal antibody. We now report a major step toward eliminating the need to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
372
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(374 citation statements)
references
References 50 publications
(55 reference statements)
2
372
0
Order By: Relevance
“…The SB system we employed here is frequently used for gene delivery and longterm transgene expression due to its lower cost and better safety profile (30)(31)(32). We used the SB system to transfer HERV-K-CAR into PBMCs from BC patients and normal female donors to propagate K-CAR T cells, and showed that these cells display CAR-dependent effector function and anti-proliferative effects.…”
Section: The Profiles Of Gene Expression In Tumor Biopsiesmentioning
confidence: 99%
“…The SB system we employed here is frequently used for gene delivery and longterm transgene expression due to its lower cost and better safety profile (30)(31)(32). We used the SB system to transfer HERV-K-CAR into PBMCs from BC patients and normal female donors to propagate K-CAR T cells, and showed that these cells display CAR-dependent effector function and anti-proliferative effects.…”
Section: The Profiles Of Gene Expression In Tumor Biopsiesmentioning
confidence: 99%
“…The fundamental idea of an "off-the-shelf" CAR T cell is a genetically edited CAR T cell with deleted endogenous αβ TCR and HLA molecules which can be achieved by the zinc finger nuclease technology [64]. Such CAR T cells are expected to be applied to a number of patients without causing graft-versus-host disease (GvHD) and without being eliminated by the host immune cells while providing CAR-mediated effector functions against cancer cells.…”
Section: Universal Car T Cellsmentioning
confidence: 99%
“…The ability to use banked CAR T-cells, generated from non-HLA matched donors in an 'off-the-shelf' manner has been an attractive prospect that has driven attempts to overcome HLA-barriers, both in terms of allo-reactivity from infused cells and host-mediated rejection [6][7][8]. T-cells encode highly specific heterodimeric αβ T-cell receptors, and these are the key mediators of major histocompatibility complex (MHC) recognition leading to GVHD.…”
mentioning
confidence: 99%
“…T-cells encode highly specific heterodimeric αβ T-cell receptors, and these are the key mediators of major histocompatibility complex (MHC) recognition leading to GVHD. Strategies to disrupt T-cell receptor (TCR) expression have used a variety of reagents including RNA interference (RNAi) [9] and targeted gene disruption using directed DNA nucleases such as Zinc Finger Nucleases [6,7], Meganucleases [10], MegaTALs [11,12], and Transcription activator like effector nucleases (TALENs) [8,13,14]. The latter operate at the genomic level, directing engineered endonucleases to highly specific loci to create double stranded DNA cleavage.…”
mentioning
confidence: 99%